If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -1 = 5p + -10 Reorder the terms: -1 + 2p = 5p + -10 Reorder the terms: -1 + 2p = -10 + 5p Solving -1 + 2p = -10 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. -1 + 2p + -5p = -10 + 5p + -5p Combine like terms: 2p + -5p = -3p -1 + -3p = -10 + 5p + -5p Combine like terms: 5p + -5p = 0 -1 + -3p = -10 + 0 -1 + -3p = -10 Add '1' to each side of the equation. -1 + 1 + -3p = -10 + 1 Combine like terms: -1 + 1 = 0 0 + -3p = -10 + 1 -3p = -10 + 1 Combine like terms: -10 + 1 = -9 -3p = -9 Divide each side by '-3'. p = 3 Simplifying p = 3
| 8z+22+13z=71 | | 9a=-9a^2-18 | | 11w=3740 | | 5+4*8= | | 14+(17+b)= | | 1+lx+1= | | 8x+14=126 | | 5(9g+2)=50 | | 2a=a+40 | | cos(3x-20)=sin(5x+6) | | f-1=-3x^2+2x-7 | | 8q^2+4q=7q^2-2q+27 | | 13d+6=6d+27 | | 3(x-9)=-10.8 | | 3(x-9)=10.8 | | 7(a+5)=73.5 | | y-54=7t | | X^2+12x-9= | | 43.2=6c-9 | | an=15+3(n-3) | | 7e-1=15.8 | | -10x+9y=11 | | 6x^4-12x^3=0 | | 3p=29.1 | | h-25=36 | | 3k+2(3k+2)=49 | | 2x+12+38=80 | | 5v^2-11v-12=0 | | -5x+2y=-14 | | 0.66+1=4x-0.33 | | -4(n+7)-6n=-98 | | -5x-3=-20 |